Tin Dioxide Thin Films As Carbon Monoxide Sensor - Yati B Yuliyati; Rubianto A Lubis; Atiek R Noviyanti; Nia Kurniatin (Pascasarjana Universitas Negeri Medan, 2017)
Abstract: This research aims to create SnO2 thin films that have the size of micrometers to nanometers for detecting CO gas. The method used in this research is a sol-gel method where all precursors such as tin dichloride, distilled water, ethanol, and ammonium fluoride 5%-10% (w/w) are mixed together to form a colloidal system. The colloidal systems with the addition of palladium are precipitated on a glass substrate. The substrate is heated at the temperature of 70oC and 100oC. Then the resistance value is determined using the avometer. The SnO2 thin films are characterized by SEM and XRD. The result of this research is that SnO2 thin films show the best sensitivity in colloidal systems with the addition of ammonium fluoride 10% (w/w). The result of the characterization of SEM and XRD concludes that SnO2 thin films can be obtained by a sol-gel method with a nanometer-scale size and it can respond to the CO gas. Keywords: carbon monoxide, metal oxides, sol-gel method, thin films